KOMPARASI JUMLAH HASIL TANGKAPAN JARING INSANG DASAR PADA DAERAH KARANG DAN LAMUN DI DESA LEBETAWI, KOTA TUAL - Jacobus Bunga Paillin; Haruna Haruna; Kedswin G. Hehanussa; Frentje Silooy (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2024)
Bottom gillnet is a fishing gear which is operated in the morning, afternoon, and evening in the waters around Lebetawi Village. However, there is limited information about the specific composition of catch, especially the differences of catch between coral and seagrass areas. The aim of this study is to compare the number of catches from coral and seagrass areas and how the fish were first caught. The research was conducted for two months, from December 2023 to January 2024, in the waters of Lebetawi Village, Tual City, Southeast Maluku Regency. Data was collected from precisely observation on bottom gillnet aperated at seagrass and coral habitatss. The catches consisted of 18 species, with total 220 individuals fish and weight 34,161.18 grams. Throughout the fishing operations at both habitats, all demersal and pelagic fish were captured by way of gilled and wedged.